PENGEMBANGAN MODUL PELATIHAN TATA RIAS PENGANTIN JUNGPARA (Beauty and Beauty Health Education, 2021)
Abstract. Jungpara bridal make-up is one kind of bridal make-up in Jepara Regency. This make-up describes the geographical situations and historical journey of Jepara’s culture. Nevertheless, this bridal make-up is not well-known by the public and make-up artists. One of solution to introduce and preserve Jungpara bridal make-up is by creating a training module about it with the aim that it can be used by the bridal make up Course and Training Institute (LKP) as a reference for deeping Jungpara bridal make-up, beside that it can also use Jungpara make-up practically, specifically for HARPI member in Jepara Regency. This research aims to discovering the result of the module development, the module validity, and the effectiveness of using the module. Research and Development method was applied in this research. The product validity was assessed by the material expert and teaching media expert. The trials of the module were conducted by 10 members of Indonesian Bridal Make-up Association (HARPI) Melati in Jepara Regency. The data collections of the study were interview, observation, documentation, questionnaire, and test. Validity assessment sheets for media expert and material expert were used as the research instruments. Descriptive percentage and N-Gain test were the techniques of data analysis. The results of the development of Jungpara bridal make-up module consisted of Module A, contained syllabus and an information book, and Module B, contained a workbook and an assessment book. This Jungpara module validity was valid based on the media expert assessment with the percentage of 86,4% and the material expert assessment with the score 98,3%. According to the pre-test and post-test, it could be stated that the mean score of N-Gain was 0,81 that could be categorized as high criterion. Keywords: module, training, makeup, Jungpara bridal Abstrak. Tata Rias Pengantin Jungpara merupakan salah satu pengantin yang ada di Kabupaten Jepara. Namun corak tata rias pengantin ini belum banyak dikenal oleh masyarkat dan perias. Salah satu upaya untuk melestarikan dan memperkenalkan tata rias ini adalah dengan menyusun modul pelatihan tentang tata rias pengantin jungpara dengan tujuan agar dapat digunakan oleh Lembaga Kursus dan Pelatihan (LKP) Rias Pengantin sebagai acuan untuk memperdalam tata rias pengantin Jungpara, selain itu dapat digunakan oleh perias, khususnya anggota HARPI Kabupaten Jepara. Penelitian ini bertujuan untuk mengetahui hasil pengembangan modul, validitas modul dan efektivitas dari penggunaan modul. Metode penelitian yang digunakan adalah Penelitian dan Pengembangan (Research and Development). Validitas produk dilakukan oleh ahli materi dan ahli media, uji coba produk dilakukan oleh 10 anggota Himpunan Ahli Rias Pengantin Indonesia (HARPI) Melati Kabupaten Jepara. Pengumpulan data menggunakan teknik wawancara, observasi, dokumentasi, angket, dan tes. Instrumen penelitian yang digunakan untuk mengumpulkan data adalah lembar penilaian validitas untuk ahli media dan ahli materi. Teknik analisis data menggunakan deskriptif persentase dan uji n-gain. Hasil dari pengembangan modul, Modul Tata Rias Pengantin Jungpara terdiri dari Modul A (Silabus dan Buku Informasi) dan Modul B (Buku Kerja dan Buku Penilaian). Validitas modul tata rias pengantin jungpara dinyatakan valid oleh ahli media dengan dengan persentase penilaian 86,4% dan persentase penilaian 98,3% dari ahli materi. Berdasarkan hasil pre test dan post test yang dilakukan sebelum dan sesudah penggunaan modul dinyatakan efektif, hal ini dilihat dari nilai rata-rata N-Gain 0,81 dengan kriteria tinggi. Kata Kunci: modul, pelatihan, tata rias, pengantin jungpara